The Relationship Between Diabetes Self-Management And The Stress Level Of Diabetes Mellitus Patients Undergoing A Diet At The Puskesmas Kota Rantau Prapat - Nainggolan, Syahrul Handoko; Silaban, Nataria Yanti; Sangkut, Sangkut (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
Diabetes Mellitus (DM) is a chronic disease characterized by blood glucose levels exceeding normal and disturbances of carbohydrate, fat and protein metabolism caused by relative or absolute deficiency of the hormone insulin. If this is left uncontrolled, it can lead to acute metabolic complications and long-term vascular complications, both microangiopathy and macroangiopathy (Darmono in Hasdianah, 2012). Knowledge is needed by DM patients to improve self diabetes management to prevent acute complications and reduce risk long term complications. People with DM must have a fairly strict diet. This can be boring and stressful because the patient has to follow the recommended diet during his lifetime. Methods: This study aims to determine the existence of The relationship between diabetes self-management and stress levels on a diet for DM patients at the Rantau Prapat Public Health Center. This study used a cross sectional design. Respondents were selected from five Puskesmas in Puskesmas Rantau Prapat using purposive sampling method. A total of 37 respondents with DM participated in the study. Data were collected using a diabetes diet knowledge questionnaire, diet self-management questionnaire, and a stress level questionnaire undergoing a DM diet, and then the data were analyzed using the Chi Square test with a significance level of <0.05. Results: The results showed that there was a relationship between diabetes self-management and the stress level of undergoing a DM diet (p=0.004). Future research is expected to be able to use respondents with a wider area and use better measuring tools.